Metode Simulasi Pembelajaran dalam Perspektif Islam - Afiful Ikhwan (Postgraduate Program Magister Pendidikan Agama Islam, 2017)
The simulation method has own characteristic it self and can be used for specific fields. In Islam, the phase of occurance process on l learning has been exemplified by Muhammad prophet SAW, that is integration process between students and teachers to get learning goal where happend on particular place and particular time. We can get some benefits from Rasulullah has been exemplified: a) when that question is asked, it can give motivation for listener to answer that question; b) question can make listener get stunt from speaker; c) asking question can achieve three-aspect moral goal and education, they are cognitive, emotion and kinetic; d) question can be more emphasis information or knowledge; e) question can make stimuli for listeners so they will be enthusiastic to know about the answer.